AC-Protection in the Context of AC/DC-Hybrid Lines - Prommetta, Jonas; Schindler, Jakob; Jäger, Johann; Keil, Timo; Butterer, Christoph (APAP 2019 - 8th IEEE International Conference on Advanced Power System Automation and Protection, 2019)
AC/DC-hybrid lines are transmission systems with AC- and DC-line conductors on the same support structure. The added DC-conductors have a significant influence on the parallel AC-conductors - especially on the AC-protection. Studies of this aspect were not found in the literature. Therefore, all relevant fault types were examined and an overview of the influencing factors on the protection of the parallel AC lines is given. The analysis of pure DC line faults shows that an unwanted trip of the ground-fault detection of the AC-protection can occur due to the electromagnetic coupling. In addition, the difficulties of the AC-protection in detecting certain intersystem faults are presented. Finally, current issues and challenges on the way to a secure operation of AC/DC-hybrid lines are outlined.
CRIS-Team Scopus Importer:2021-04-20
Keywords: AC/DC-hybrid line; AC/DC-protection coordination; electromagnetic coupling; intersystem faults; VSC-HVDC